1997
DOI: 10.1136/hrt.77.3.219
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of intention to treat decisions for invasive therapy in coronary artery disease in The Netherlands.

Abstract: Objective-To determine the appropriateness of intention to treat decisions concerning coronary artery bypass grafting (CABG) and percutaneous transluminal coronary angioplasty (PTCA) for patients with coronary artery disease in The Netherlands. Design-Prospective study of intention to treat decisions using a computerised expert system. Setting-"Presentation" sessions in 10 tertiary referral heart centres in 1992.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Expert panels' ratings of the appropriateness of revascularization in patients with a variety of typical indications, determined according to the RAND-University of California at Los Angeles (UCLA) method, make this judgment explicit, by making it possible to assign patients a score on a scale that ranges from appropriate through uncertain to inappropriate. Studies using this method have shown that overuse [2][3][4][5][6][7][8][9][10][11] of invasive techniques in the management of coronary disease is uncommon, and attention has turned to the issue of underuse. [12][13][14][15][16] Well-designed expert panels can closely reflect the views of practicing physicians, 17 and methods for detecting the underuse of revascularization are highly reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…Expert panels' ratings of the appropriateness of revascularization in patients with a variety of typical indications, determined according to the RAND-University of California at Los Angeles (UCLA) method, make this judgment explicit, by making it possible to assign patients a score on a scale that ranges from appropriate through uncertain to inappropriate. Studies using this method have shown that overuse [2][3][4][5][6][7][8][9][10][11] of invasive techniques in the management of coronary disease is uncommon, and attention has turned to the issue of underuse. [12][13][14][15][16] Well-designed expert panels can closely reflect the views of practicing physicians, 17 and methods for detecting the underuse of revascularization are highly reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…For bypass surgery, where the risk of adverse events on the waiting list is greatest, the inappropriate rate ranged from 2% in New York State to 8% in Sweden, with 5% of cases inappropriate in the Netherlands. The appropriateness of PTCA was more questionable with about 40% of cases at each site judged uncertain in appropriateness [14,15] (Swedish Council on Technology Assessment in Health Care, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Data were reviewed for completeness and accuracy before being entered into the computerized data base. Additional details regarding the way cases were selected, data collected and confidentiality maintained are described elsewhere [13][14][15].…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations